2019
DOI: 10.1371/journal.pone.0215866
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors in children born with marginally low birth weight: A longitudinal cohort study up to 7 years-of-age

Abstract: Introduction Low birth weight (LBW, <2500 g) may predict an increased risk of an adverse cardiometabolic profile later in life, but long-term effects in different populations and birth weight strata are still unclear. We explored laboratory markers of cardiometabolic risk in children born with marginally LBW (2000–2500 g). Methods This was a prospective longitudinal cohort study including 285 Swedish marginally LBW children and 95 normal birth weight (NBW, 2501–4500 g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In categories of birth weight, higher levels of apoB were associated with lower birth weight [16]. On the other hand, Starnberg et al, in their study among Swedish children of 7 years of age, did not show any significant association between low birth weight and apoB or apoA1 levels [17].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In categories of birth weight, higher levels of apoB were associated with lower birth weight [16]. On the other hand, Starnberg et al, in their study among Swedish children of 7 years of age, did not show any significant association between low birth weight and apoB or apoA1 levels [17].…”
Section: Discussionmentioning
confidence: 78%
“…This could be interpreted that adults born with lower birth weight relative to gestational age may have higher apoB and lower apoA1 levels in adulthood, a documented risk pattern for CVD in the Swedish population [5]. This study is one of the few that explored such associations [15][16][17], and the largest so far. Barker et al also reported higher apoB levels in children born with low birth weight [16] and highlighted that impaired growth of the liver in late gestation leads to permanent changes in the low-density lipoprotein cholesterol metabolism [16].…”
Section: Discussionmentioning
confidence: 86%
“…They proved that the SGA group demonstrated a significantly higher level of the mean fasting glucose than the control group. But there were no considerable differences in insulin, HOMA-IR (homeostatic model assessment for insulin resistance), blood lipid levels between SGA and AGA groups [29].…”
Section: Discussionmentioning
confidence: 92%
“…A positive correlation between elevated levels of total cholesterol, LDL cholesterol and apolipoprotein B in adults born as SGA and a small abdominal circumference observed in the newborn after birth was also revealed [22]. There are relatively few reports referring to research on lipids and/or lipoproteins in the blood serum of SGA children [21,[23][24][25][26][27][28][29]. Although their results vary depending on the studied population, it is worth emphasizing that the assessment of the lipid profile in SGA children is recommended in certain regions [30].…”
Section: Introductionmentioning
confidence: 99%

Lipid Profile in Children Born Small for Gestational Age

Zamojska,
Niewiadomska-Jarosik,
Kierzkowska
et al. 2023
Preprint
“…The prevalence of LBW is also a predictor of future health outcomes as these infants are at higher risk for various health issues, including developmental delays, chronic diseases, and cognitive deficits (Moura‐Dos‐Santos et al, 2013; Souza et al, 2022; Whitman et al, 2022). The ripple effects of LBW are felt not only in terms of increased healthcare expenditure but also through the potential diminishment of human capital and productivity (Starnberg et al, 2019; Tchamo et al, 2016; Venero‐Fernández et al, 2017). Thus, examining and addressing the prevalence of LBW and its risk factors becomes essential for not only safeguarding the health of infants but also promoting the well‐being and prosperity of society.…”
Section: Introductionmentioning
confidence: 99%